2018
DOI: 10.1596/1813-9450-8425
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Development in Sub-Saharan Africa: A Scorecard

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 23 publications
0
31
0
3
Order By: Relevance
“…However, Calderon et al (2018) estimate that people with access to electricity grew from 14% in 1990 to about 35% in 2014. Foster and Briceno-Garmenda (2009) and Estache and Garsous (2012) conclude that power or energy production presents the largest infrastructure gap for Africa, requiring nearly 40% to 60% of infrastructure investment.…”
Section: State Of Infrastructure In Sub-sahara Africamentioning
confidence: 99%
See 1 more Smart Citation
“…However, Calderon et al (2018) estimate that people with access to electricity grew from 14% in 1990 to about 35% in 2014. Foster and Briceno-Garmenda (2009) and Estache and Garsous (2012) conclude that power or energy production presents the largest infrastructure gap for Africa, requiring nearly 40% to 60% of infrastructure investment.…”
Section: State Of Infrastructure In Sub-sahara Africamentioning
confidence: 99%
“…In 2009, approximately 90% of Africa's urban population lived within reach of a mobile network, compared to 48% in the rural areas. Internet density, represented by number of users per 100 people, is also estimated to have increased from 1.3 people in 2005 to 16.7 people in 2015 (Calderon et al, 2018). Williams et al (2011) The distinct lack of an effective transportation system in sub-Saharan Africa is one of the greatest impediments to growth and poverty reduction (Beuran et al, 2015).…”
Section: State Of Infrastructure In Sub-sahara Africamentioning
confidence: 99%
“…According to the Global Competitive Report, 2018, SSA scored 46.3 out of a possible 100 points, ranking it last globally [10]. Additionally, there has been minimal addition of electricity generating capacity over the last 20 years in the region, increasing by 0.01 MW per 1,000 people in 2012 from 0.03 MW in 1990 [11]. Many factors contribute to this trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, African nations, till the 1970s, enjoyed a relative era of prosperity, but the structural adjustment plans and other factors like low commodity prices (raw materials) and the Franc CFA currency devaluation (in 1994) led to severe economic crises (in Figure 1, the decline in the trade balance in Senegal from 1995), preventing them from investing in the development of infrastructure. This partly explains why Africa lags behind in transport development [6]. The state of the transportation sector was exposed in previous work, in which it is shown that African transport systems still need improvement [3,7].…”
Section: Introductionmentioning
confidence: 97%